Comparison of Long Term Outcomes After Endovascular Treatment Versus Bypass Surgery in Chronic Limb Threatening Ischaemia Patients with Long Femoropopliteal Lesions. (February 2021) - Zlatanovic, Petar; Mahmoud, Amr A.; Cinara, Ilijas; Cvetic, Vladimir; Lukic, Borivoje; Davidovic, Lazar
Abstract : Objective: There are currently two treatments available for patients with chronic limb threatening ischaemia (CLTI): open surgical bypass (OSB) and percutaneous transluminal angioplasty with/without stenting (PTA/S). The aim of this study was to compare short and long term outcomes between PTA/S and OSB in CLTI patients with long (GLASS grade III and IV) femoropopliteal disease. Methods: This was a two centre retrospective study including all consecutive patients with CLTI undergoing first time lower extremity intervention at two distinct vascular surgical centres. Between 1 January 2012 and 1 January 2018, 1 545 CLTI consecutive limbs were treated for femoropopliteal GLASS grade III and IV lesions at two vascular surgical centres. Using covariables from baseline and angiographic characteristics, a propensity score was calculated for each limb. Thus, comparable patient cohorts (235 in PTA/S and 235 in OSB group) were identified for further analysis. The primary outcomes were freedom from re-intervention in the treated extremity and major amputation. Secondary outcomes were all hospital complications among the two patient groups. Results: Total overall complication rates were significantly higher in the OSB group (20.42% vs. 5.96%, p < .001), especially wound infection/seroma rate that required prolonged hospitalisation and further treatment (7.65% vs. 0%, p < .001). After the median follow up of 61 months, re-intervention rates were significantly higher in the PTA/S group (log rank test, 44.68% vs. 29.79%, p = .002), but there was no significant difference in terms of major amputation rates between the two group of patients (log rank test, PTA/S 27.23% vs. OSB 22.13%, p = .17). Conclusion: Bypass surgery seems to be superior to PTA/S for GLASS grade III and IV femoropopliteal lesions in patients with CLTI in terms of long term re-intervention rates, but with considerably higher rates of post-operative complications. A larger cohort of patients in currently ongoing randomised trials, as well as prospective cohort studies are necessary to confirm these findings.